2018
DOI: 10.3390/rs10101501
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Airborne Antenna Geometry for Ocean Surface Scatterometric Measurements

Abstract: We consider different antenna configurations, ranging from simple X-configuration to multi-beam star geometries, for airborne scatterometric measurements of the wind vector near the ocean surface. For all geometries, track-stabilized antenna configurations, as well as horizontal transmitter and receiver polarizations, are considered. The wind vector retrieval algorithm is generalized here for an arbitrary star geometry antenna configuration and tested using the Ku-Band geophysical model function. Using Monte C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…As the water azimuthal NRCS dependence at the constant medium incidence angle is smooth and has four extremums (Figure 4), it is evident that to remove the wind direction ambiguity at a single spacecraft pass, a number of azimuthal looks for the same cell need to be increased. Recently, we have demonstrated that in case of an airborne scatterometer provided NRCS measurements at the same incidence angle, at least four star-configured antennas are required to achieve an unambiguous recovery of the sea wind direction [37]. In the case of the spacecraft scatterometer with the fixed antennas, it is impossible to realize the star geometry measurement observing the same cell as its antennas have different incidence angles and the maximum azimuthal difference of the antennas' locations is limited by the right or left swath.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the water azimuthal NRCS dependence at the constant medium incidence angle is smooth and has four extremums (Figure 4), it is evident that to remove the wind direction ambiguity at a single spacecraft pass, a number of azimuthal looks for the same cell need to be increased. Recently, we have demonstrated that in case of an airborne scatterometer provided NRCS measurements at the same incidence angle, at least four star-configured antennas are required to achieve an unambiguous recovery of the sea wind direction [37]. In the case of the spacecraft scatterometer with the fixed antennas, it is impossible to realize the star geometry measurement observing the same cell as its antennas have different incidence angles and the maximum azimuthal difference of the antennas' locations is limited by the right or left swath.…”
Section: Resultsmentioning
confidence: 99%
“…Recently in [37], we have demonstrated that in order to provide an accurate and unambiguous retrieval of the wind vector, at least four azimuthally star-configured beams (looks) are required at the same incidence angle. The airborne star geometry [38] and some other earlier considered airborne one- [39] or multi-beam [40][41][42][43] geometries or sector scanning airborne instruments operated in the scatterometer mode [44][45][46][47][48][49] cannot be implemented for the satellite scatterometer to observe the same cell and to achieve better sea ice and water discrimination.…”
Section: Methodsmentioning
confidence: 99%
“…We have considered the airborne weather radar, FM-CW millimeter wave demonstrator system, and airborne Doppler navigation system equipped with a fixed-beam antenna performing measurements at the circular ground track [23,[25][26][27]. Also, we have studied the wind measurements by the airborne weather radar in the scanning-beam case, and by the airborne Doppler navigation system and multi-beam scatterometer in the multi-beam case at the rectilinear ground track [24,[28][29][30]. The research has shown that, in the general case, the wind speed and direction can be found using the system of N equations composed for the appropriate NRCSs obtained at the same incidence angle for each azimuth sector observed with the given azimuth step [30]:…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, VV polarization provides a smaller difference between the largest and second largest maxima compared to the HH polarization scenario at medium incidence angles [32] that is not in favor of the ambiguity's removal. Recently, we have shown that for an accurate and unambiguous estimation of the wind direction (as well as the wind speed) at least four star-configured beams are needed to perform the wind vector retrieval at the same incidence angle [33]. However, satellite scatterometer measurements cannot provide the necessary star geometry observation for the same cell (and at the same incidence angle).…”
Section: Methodsmentioning
confidence: 99%